Estudo comparativo de métodos analíticos visando a determinação de elementos traço em material particulado atmosférico - Lemos, Melina do Espírito Santo (2021)
Atmospheric particulate matter is directly related to air pollution and, as its constituents are particles of very small diameter, when inhaled, it can cause health problems, especially respiratory and cardiac problems. The trace elements associated with this material can aggravate clinical health problems, thus requiring that they be monitored. For the determination of these elements, several techniques can be used, including atomic spectrometry, which normally requires that the samples to be in solution form, making the sample preparation an important step. That said, for the determination of Al, Fe and Zn, by optical spectrometry with inductively coupled plasma, and As, Cd, Cr, Cu, Mn, Pb and Ti, by inductively coupled plasma mass spectrometry, different strategies for the sample preparation of Atmospheric particulate matter samples were evaluated ultrasound-assisted extraction and microwave-assisted decomposition. For decomposition, the use of diluted HNO3 as well as the use of a concentrated acid mixture (HNO3, HCl and HF) were studied. Initially, the methods were optimized using multivariate designs. For ultrasound-assisted extraction, a better efficiency was found when 7.5 mL of 2 mol L-1 HCl and 7.5 mL of H2O were used at 40°C for 7 minutes. In the decomposition with dilute acid, a better efficiency was obtained using 6 mL of HNO3 10 mol L-1 , 2 mL of H2O2 and 2 mL of H2O. For the decomposition with the acid mixture, the optimal condition was found when 6.5 mL of HNO3, 2 mL of HCl and 1.5 mL of HF were used. All optimized methods resulted in good sensitivity, with low detection and quantification limits. The methods showed good accuracy for As, Cd, Cu and Pb, with recoveries above 80%, when addition and recovery tests were performed. Good agreement with the certified values in reference materials ERM CZ-120 and NIST 1648a was also found for these elements. For Mn a good agreement was obtained when acid decomposition assisted with microwave radiation was used, both with dilute acid and acid mixture. Finally, for Al, Cr and Ti, accuracy was only obtained when more energetic conditions, such as higher temperature and concentrated acids, were used. Therefore, considering the determination of potentially toxic elements such as As, Cd, Cu and Pb, ultrasound-assisted acid extraction is a simple, fast and efficient method for analyzing atmospheric particulate matter. However, to determine elements more strongly bound to the matrix, such as Al, Cr, Mn and Ti, the microwave-assisted decomposition method and the use of HNO3, HF and HCl becomes necessary.